Conversion of invisible metal-organic frameworks to luminescent perovskite nanocrystals for confidential information encryption and decryption. Issue 1 (December 2017) - Zhang, Congyang; Wang, Bo; Li, Wanbin; Huang, Shouqiang; Kong, Long; Li, Zhichun; Li, Liang
Abstract Traditional smart fluorescent materials, which have been attracting increasing interest for security protection, are usually visible under either ambient or UV light, making them adverse to the potential application of confidential information protection. Herein, we report an approach to realize confidential information protection and storage based on the conversion of lead-based metal-organic frameworks (MOFs) to luminescent perovskite nanocrystals (NCs). Owing to the invisible and controlled printable characteristics of lead-based MOFs, confidential information can be recorded and encrypted by MOF patterns, which cannot be read through common decryption methods. Through our conversion strategy, highly luminescent perovskite NCs can be formed quickly and simply by using a halide salt trigger that reacts with the MOF, thus promoting effective information decryption. Finally, through polar solvents impregnation and halide salt conversion, the luminescence of the perovskite NCs can be quenched and recovered, leading to reversible on/off switching of the luminescence signal for multiple information encryption and decryption processes. Materials with switchable fluorescence possess great potential for information encryption applications, but systems where the off state is invisible are lacking. Here the authors print patterns of colourless metal organic frameworks and reversibly transform these inks into fluorescent perovskite nanocrystals